Characterization And Modeling Of Pultruded Jute Fibre Reinforced Unsaturated Polyester Composite - Safiee, Sahnizam (2011)
Pultruded Jute Fibre Reinforced Unsaturated Polyester Composites (PJFRC) was prepared and examined stage by stage in this study.Komposit Gentian Jut Terpultrisi diperkuat Poliester tak tepu (PJFRC) telah disediakan dan diuji secara berperingkat dalam kajian ini.